Resin-based porous carbon material, method for preparing the same, and use thereof
Patent Information
- Application Number
- CN202611062910.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-13
AI Technical Summary
然而,树脂基多孔碳的规模化生产仍面临诸多挑战:在结构方面,普遍存在孔道连通性差、高温热处理后表面官能团易失活等问题;在制备工艺方面,化学活化法常伴随强碱对碳骨架的腐蚀,物理活化法则存在介孔率调控难度大的局限,而模板法则因模板剂成本高、去除过程中可能残留杂质等问题,制约了其进一步应用
[0017]本发明首先通过第一次水热反应,制得具有稳定碳骨架结构的预交联树脂。在此基础上,在第二次水热反应过程中,采用短时高压条件,使水达到特定的超临界水状态,利用超临界水触发机制促使酚醛树脂分子间的氢键快速断裂,在羟甲基的调控作用下,酚醛树脂形成的纳米颗粒定向堆叠,实现了非平衡态下交联反应与颗粒定向堆叠的同步构建,从而形成具有高力学强度且微孔均匀的碳骨架,同时,超临界水对酚醛树脂进一步活化生成介孔结构,通过协同控制预交联树脂的凝胶分数、反应的温度、时间和压力,使其满足特定的热压交联耦合指数,精准调控出微孔-介孔的复合结构,使得树脂基多孔碳材料具备优异的力学性能;另外,超临界水环境中的溶解氧与酚醛树脂衍生的小分子羧酸共同作用,在材料表面引入羧基化修饰,显著增强树脂基多孔碳材料的亲水性,进而提升其电化学活性。
Smart Images

Figure CN122897386A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of porous carbon materials technology, and in particular to a resin-based porous carbon material, its preparation method, and its application. Background Technology
[0002] With the explosive growth of the electric vehicle and energy storage industries, porous carbon, due to its high specific surface area, tunable pore structure, and excellent conductivity, has become a core material for improving battery energy density, power density, and cycle stability. Compared to biomass and pitch-based porous carbon, resin-based porous carbon has become the main source of porous carbon due to its advantages such as small pore size distribution deviation, high mesopore ratio, and stable specific surface area. It has now become the preferred material for silicon-carbon anodes, supercapacitor electrodes, and solid-state battery interface layers. However, the large-scale production of resin-based porous carbon still faces many challenges: in terms of structure, it generally suffers from poor pore connectivity and easy deactivation of surface functional groups after high-temperature heat treatment; in terms of preparation process, chemical activation methods are often accompanied by strong alkali corrosion of the carbon skeleton, physical activation methods are limited by the difficulty in controlling mesopore ratio, and template methods are restricted from further application due to the high cost of template agents and the possibility of residual impurities during removal. Summary of the Invention
[0003] Therefore, it is necessary to provide a resin-based porous carbon material, its preparation method, and its application to address the above problems. The preparation method can not only precisely control the pore structure of the porous carbon material, but also endow the material with higher activity through surface modification. At the same time, the manufacturing process is green and environmentally friendly, with significant process and environmental advantages.
[0004] A method for preparing a resin-based porous carbon material includes the following steps:
[0005] Phenolic resin was mixed with water and subjected to a first hydrothermal reaction to obtain a pre-crosslinked resin.
[0006] The pre-crosslinked resin is mixed with water to carry out a second hydrothermal reaction to obtain a resin-based porous carbon material. During the second hydrothermal reaction, the system pressure reaches more than 20 MPa within 5 minutes.
[0007] The gel fraction G of the pre-crosslinked resin, the system pressure P of the second hydrothermal reaction, the reaction temperature T of the second hydrothermal reaction, and the reaction time t of the second hydrothermal reaction satisfy the following relationship: K=(P×T×t) / G, where K is the thermo-compression crosslinking coupling index, and the value of K ranges from 250 to 1500.
[0008] In one embodiment, the gel fraction G of the pre-crosslinked resin is 50% to 85%.
[0009] In one embodiment, the temperature of the first hydrothermal reaction is 150°C to 200°C, and the time is 3 hours to 7 hours.
[0010] In one embodiment, the mass ratio of the phenolic resin to water is 1:5 to 1:15.
[0011] In one embodiment, during the second hydrothermal reaction, the system pressure reaches 20 MPa to 60 MPa within 5 minutes.
[0012] In one embodiment, the reaction temperature T of the second hydrothermal reaction is 500°C to 700°C.
[0013] In one embodiment, the reaction time t of the second hydrothermal reaction is 1h to 3h.
[0014] In one embodiment, the mass ratio of the pre-crosslinked resin to water is 1:5 to 1:20.
[0015] A resin-based porous carbon material prepared by the method described above has micropores with a diameter of less than 2 nm, mesopores with a diameter of 2 nm to 8 nm, a micropore to mesopore ratio of 4:1 to 4:3, and a specific surface area of 1400 m². 2 / g~2200m 2 / g.
[0016] Application of a resin-based porous carbon material as described above in silicon-carbon anodes, supercapacitive electrodes, or solid-state batteries.
[0017] This invention first prepares a pre-crosslinked resin with a stable carbon skeleton structure through a first hydrothermal reaction. Based on this, a second hydrothermal reaction is conducted under short-duration, high-pressure conditions to bring the water to a specific supercritical water state. The supercritical water trigger mechanism promotes the rapid breaking of hydrogen bonds between phenolic resin molecules. Under the regulation of hydroxymethyl groups, the nanoparticles formed by the phenolic resin are directionally stacked, achieving simultaneous construction of the crosslinking reaction and particle directional stacking under non-equilibrium conditions. This results in a carbon skeleton with high mechanical strength and uniform micropores. Simultaneously, supercritical water further activates the phenolic resin to generate a mesoporous structure. By synergistically controlling the gel fraction of the pre-crosslinked resin, the reaction temperature, time, and pressure, a specific thermo-compound crosslinking coupling index is achieved, precisely controlling the microporous-mesoporous composite structure. This gives the resin-based porous carbon material excellent mechanical properties. Furthermore, the dissolved oxygen in the supercritical water environment interacts with the small-molecule carboxylic acid derived from the phenolic resin to introduce carboxylation modification on the material surface, significantly enhancing the hydrophilicity of the resin-based porous carbon material and thus improving its electrochemical activity.
[0018] The preparation method of this invention uses only water and phenolic resin as reactants, without the need to add other chemical reagents, thus eliminating the generation of harmful and hazardous waste at the source and achieving the green and efficient preparation of resin-based porous carbon materials. In summary, the resin-based porous carbon material preparation method of this invention can not only precisely control the pore structure of porous carbon materials, but also impart higher electrochemical activity to resin-based porous carbon materials through surface modification. Furthermore, the manufacturing process is green and environmentally friendly, exhibiting significant process and environmental advantages. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1 This is a scanning electron microscope image of the resin-based porous carbon material prepared in Example 1 of the present invention;
[0021] Figure 2 The nitrogen adsorption-desorption curve of the resin-based porous carbon material prepared in Example 1 of this invention is shown. Detailed Implementation
[0022] To facilitate understanding of the present invention, it will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. Rather, these embodiments or examples are provided to make the disclosure of the present invention more thorough and complete.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments or examples only and is not intended to limit the invention. The optional scope of the term "and / or" as used herein includes any one of two or more of the related listed items, as well as any and all combinations of the related listed items, including any two related listed items, any more related listed items, or a combination of all related listed items.
[0024] In this invention, numerical ranges are involved. Unless otherwise specified, the numerical ranges are considered continuous and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe features or characteristics, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are included.
[0025] The method for preparing resin-based porous carbon materials provided by the present invention includes the following steps:
[0026] Phenolic resin was mixed with water and subjected to a first hydrothermal reaction to obtain a pre-crosslinked resin.
[0027] The pre-crosslinked resin is mixed with water and subjected to a second hydrothermal reaction to obtain a resin-based porous carbon material. During the second hydrothermal reaction, the system pressure P reaches above 20 MPa within 5 minutes. The gel fraction G of the pre-crosslinked resin, the system pressure P of the second hydrothermal reaction, the reaction temperature T of the second hydrothermal reaction, and the reaction time t of the second hydrothermal reaction satisfy the following relationship: K = (P × T × t) / G, where K is the thermo-compression crosslinking coupling index, with a value ranging from 250 to 1500; the system pressure P of the second hydrothermal reaction is in MPa; the reaction temperature T of the second hydrothermal reaction is in °C; the reaction time t of the second hydrothermal reaction is in h; and the gel fraction of the pre-crosslinked resin is in [missing information].
[0028] This invention first prepares a pre-crosslinked resin with a stable carbon skeleton structure through a first hydrothermal reaction. Based on this, a second hydrothermal reaction is performed under short-duration, high-pressure conditions to achieve a relative permittivity of 5-20 and an ion product of 10 for the water. -7 ~10 -9In the supercritical water state, the hydrogen bonds between phenolic resin molecules are rapidly broken by the supercritical water triggering mechanism. Under the regulation of hydroxymethyl groups, phenolic resin can form nanoparticles with a particle size of 45nm~55nm and be directionally stacked. This achieves the simultaneous construction of high crosslinking degree crosslinking reaction and nanoparticle directional stacking under non-equilibrium conditions, forming a three-dimensional network carbon skeleton with high mechanical strength and uniform micropores. At the same time, supercritical water further activates phenolic resin to generate mesoporous structures, precisely controlling the composite structure of micropores and mesopores, and accelerating the transformation of phenolic resin into a stable carbon structure. This is achieved through synergistic control of pre-crosslinking... The gel fraction of the resin, the temperature, time, and pressure of the reaction are adjusted to meet a specific thermo-press crosslinking coupling index. Preferably, the thermo-press crosslinking coupling index K is in the range of 250 to 1050, for example, any value among 300, 600, 900, or 1000. This allows the resin-based porous carbon material to possess a specific micropore to mesopore ratio and excellent mechanical properties under high-temperature conditions. In addition, the dissolved oxygen in the supercritical water environment works together with the small molecule carboxylic acid derived from the phenolic resin to introduce carboxylation modification on the material surface, significantly enhancing the hydrophilicity of the resin-based porous carbon material and thus improving its electrochemical activity.
[0029] The preparation method of this invention uses only water and phenolic resin as reactants, without the need for additional chemical reagents, thus eliminating the generation of harmful and hazardous waste at the source and achieving green and efficient preparation of resin-based porous carbon materials. In summary, the resin-based porous carbon material preparation method of this invention can precisely control the pore structure of porous carbon materials and endow them with higher electrochemical activity and mechanical properties. Simultaneously, the manufacturing process is green and environmentally friendly, exhibiting significant process and environmental advantages.
[0030] In order to provide a more stable pre-crosslinked resin for carbon skeleton to form a stable three-dimensional carbon skeleton structure in the second hydrothermal reaction, the gel fraction G of the pre-crosslinked resin needs to be controlled. Specifically, the gel fraction G of the pre-crosslinked resin is preferably 50% to 85%, and can be selected as any one of 50%, 60%, 65%, 70% or 85% or any range between two.
[0031] Optionally, the temperature of the first hydrothermal reaction is 150℃~200℃, which can be any value among 150℃, 160℃, 170℃, 180℃ or 200℃ or any range between two; the time of the first hydrothermal reaction is 3h~7h, which can be any value among 3h, 4h, 5h, 6h or 7h or any range between two. Within this range, a pre-crosslinked resin with a suitable gel fraction can be obtained, which is beneficial for preparing resin-based porous carbon materials with high mechanical strength and excellent pore structure in the subsequent second hydrothermal reaction.
[0032] In order to obtain a pre-crosslinked resin with high purity, the reaction product can be filtered, washed and dried after the first hydrothermal reaction. The drying temperature is preferably 100℃ and the time is 5h~10h.
[0033] In order to ensure that the phenolic resin is fully dispersed in water and undergoes a uniform pre-crosslinking reaction, and to avoid uneven crosslinking due to excessively high resin concentration or decreased reaction efficiency due to excessively low concentration, the mass ratio of the phenolic resin to water is preferably 1:5 to 1:15, and can be selected from any ratio of 1:5, 1:8, 1:10 or 1:15.
[0034] The specific amount and molecular weight of the phenolic resin used in this invention are not key limiting factors. Conventional commercially available phenolic resins can be used according to actual needs.
[0035] In the second hydrothermal reaction, preferably, the system pressure P reaches 20MPa~60MPa within 5 minutes. For example, the system pressure P reaches any value or a range between 20MPa, 25MPa, 30MPa, 35MPa, 40MPa, 45MPa, 50MPa, 55MPa or 60MPa within 5 minutes. This rapid attainment of a high-pressure state in such a short time can promote the directional stacking of phenolic resin particles to form a microporous structure and improve the crosslinking degree of the resin, thereby constructing a more stable porous three-dimensional carbon framework structure. At the same time, the supercritical water with a specific ion product and relative permittivity formed under these process conditions can introduce carboxyl functional groups onto the surface of the resin-based porous carbon material.
[0036] In order to achieve a high-pressure state through rapid heating in a very short time, thereby inducing directional recombination of phenolic resin in a critical aqueous medium and improving reaction efficiency, the mixture of pre-crosslinked resin and water can be directly placed in a high-temperature environment for a second hydrothermal reaction. The reaction temperature T of the second hydrothermal reaction is preferably 500℃~700℃, and can be any value among 500℃, 550℃, 600℃, 650℃ or 700℃ or any range between two of them.
[0037] In the second hydrothermal reaction, the high-pressure environment established in a very short time significantly increases the reaction rate, allowing the resin to crosslink rapidly. Therefore, the reaction time t of the second hydrothermal reaction can be shortened to 1h~3h, for example, any value of 1h, 1.5h, 2h or 3h or any range between two of these, which is much lower than the conventional 5h~24h. This optimization can effectively avoid the problems of cracks and brittleness in the carbon skeleton caused by prolonged hydrothermal treatment.
[0038] After the second hydrothermal reaction is completed, the reaction products can be cooled, filtered, washed and dried. The cooling process is preferably carried out by natural cooling at room temperature, so as to avoid drastic changes in the surface stress of the resin-based porous carbon material caused by excessively rapid cooling, thereby effectively preventing cracks and structural collapse.
[0039] In order to form a suitable supercritical water environment in the second hydrothermal reaction, ensure that water can fully penetrate into the interior of the pre-crosslinked resin to promote activation and pore formation, and maintain sufficient system pressure to trigger the supercritical water mechanism, the mass ratio of the pre-crosslinked resin to water is preferably 1:5 to 1:20, and can be selected from any ratio of 1:5, 1:8, 1:11, 1:14, 1:17 or 1:20.
[0040] This invention also provides a resin-based porous carbon material prepared by the above-described method, wherein the micropores in the resin-based porous carbon material have a diameter of less than 2 nm, the mesopores have a diameter of 2 nm to 8 nm, the ratio of the number of micropores to the number of mesopores is 4:1 to 4:3, and the specific surface area of the resin-based porous carbon material is 1400 m². 2 / g~2200m 2 / g.
[0041] The present invention also provides the application of the resin-based porous carbon material as described above in silicon-carbon anodes, supercapacitor electrodes or solid-state batteries.
[0042] The technical solution of the present invention will be further described below through specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating the present invention and should not be regarded as limiting the scope of the present invention. Unless otherwise specified, specific conditions in the embodiments are performed under conventional conditions or conditions recommended by the manufacturer. Reagents or instruments used without specified manufacturers are all commercially available conventional products.
[0043] Example 1
[0044] Phenolic resin was heated and melted at 50°C; then, phenolic resin and water were mixed at a mass ratio of 1:10 and placed in a hydrothermal reactor for the first hydrothermal reaction at 180°C for 10 hours; after the reaction was completed, the mixture was filtered, washed, and dried at 100°C for 5 hours to obtain a pre-crosslinked resin with a gel fraction of 68%.
[0045] Pre-crosslinked resin and water at a mass ratio of 1:11 were placed in a high-pressure reactor, and then transferred to a crucible furnace at 600℃ for a second hydrothermal reaction. During the reaction, the pressure in the high-pressure reactor was increased to 30 MPa within 5 minutes, and the reaction was maintained at this temperature for 2 hours. After the reaction was completed, the material was cooled, depressurized, filtered, washed, and dried to obtain resin-based porous carbon material.
[0046] The morphology of the resin-based porous carbon material prepared in this embodiment is as follows: Figure 1 As shown, the resin-based porous carbon material is formed by stacking uniform nanoparticles with a particle size of about 50 nm. The particles form a regular three-dimensional porous network structure with uniform pore distribution and good connectivity. Figure 2 The nitrogen adsorption-desorption curves of the resin-based porous carbon material show that the adsorption curve rises sharply in the low relative pressure region (P / P0<0.1), indicating the presence of a large number of micropores in the material. In the relative pressure range of P / P0=0.4~0.8, an H4-type hysteresis loop appears, and the desorption curve is located below the adsorption curve, indicating that the material also contains abundant mesoporous structures.
[0047] The resin-based porous carbon material prepared in this embodiment was subjected to pore size distribution test, and the pore size distribution curve was obtained. The curve shows that the pore size distribution has a single peak characteristic, with the distribution peak concentrated in the micropore range of 0.5nm~2nm, indicating that micropores are the main source of pores in the material. There is still a certain amount of distribution in the mesopore range of 2nm~8nm, but no independent peak is formed, indicating that the material has a pore structure dominated by micropores and supplemented by mesopores.
[0048] Example 2
[0049] Phenolic resin was heated and melted at 50°C; then, phenolic resin and water were mixed at a mass ratio of 1:10 and placed in a hydrothermal reactor for the first hydrothermal reaction at 180°C for 10 hours; after the reaction was completed, the mixture was filtered, washed, and dried at 100°C for 5 hours to obtain a pre-crosslinked resin with a gel fraction of 68%.
[0050] A pre-crosslinked resin and water at a mass ratio of 1:11 were placed in a high-pressure reactor, and then transferred to a crucible furnace at 500°C for a second hydrothermal reaction. During the reaction, the pressure in the high-pressure reactor was increased to 25 MPa within 5 minutes, and the reaction was maintained at this temperature for 2 hours. After the reaction was completed, the material was cooled, depressurized, washed, and dried to obtain a resin-based porous carbon material.
[0051] Example 3
[0052] Phenolic resin was heated and melted at 50°C; then, phenolic resin and water were mixed at a mass ratio of 1:10 and placed in a hydrothermal reactor for the first hydrothermal reaction at 180°C for 10 hours; after the reaction was completed, the mixture was filtered, washed, and dried at 100°C for 5 hours to obtain a pre-crosslinked resin with a gel fraction of 68%.
[0053] A pre-crosslinked resin and water at a mass ratio of 1:11 were placed in a high-pressure reactor, and then transferred to a crucible furnace at 700℃ for a second hydrothermal reaction. During the reaction, the pressure in the high-pressure reactor was increased to 50 MPa within 5 minutes, and the reaction was maintained at this temperature for 2 hours. After the reaction was completed, the material was cooled, depressurized, washed, and dried to obtain a resin-based porous carbon material.
[0054] Example 4
[0055] Phenolic resin was heated and melted at 50°C; then, phenolic resin and water were mixed at a mass ratio of 1:10 and placed in a hydrothermal reactor for the first hydrothermal reaction at 180°C for 10 hours; after the reaction was completed, the mixture was filtered, washed, and dried at 100°C for 5 hours to obtain a pre-crosslinked resin with a gel fraction of 68%.
[0056] A pre-crosslinked resin and water at a mass ratio of 1:11 were placed in a high-pressure reactor, and then transferred to a crucible furnace at 750°C for a second hydrothermal reaction. During the reaction, the pressure in the high-pressure reactor increased to 65 MPa within 5 minutes, and the reaction was maintained at this temperature for 2 hours. After the reaction was completed, the material was cooled, depressurized, washed, and dried to obtain a resin-based porous carbon material.
[0057] Example 5
[0058] Phenolic resin was heated and melted at 50°C; then, phenolic resin and water were mixed at a mass ratio of 1:10 and placed in a hydrothermal reactor for the first hydrothermal reaction at 180°C for 10 hours; after the reaction was completed, the mixture was filtered, washed, and dried at 100°C for 5 hours to obtain a pre-crosslinked resin with a gel fraction of 68%.
[0059] A pre-crosslinked resin and water at a mass ratio of 1:11 were placed in a high-pressure reactor, and then transferred to a crucible furnace at 600℃ for a second hydrothermal reaction. During the reaction, the pressure in the high-pressure reactor was increased to 30 MPa within 5 minutes, and the reaction was maintained at this temperature for 1 hour. After the reaction was completed, the material was cooled, depressurized, washed, and dried to obtain a resin-based porous carbon material.
[0060] Example 6
[0061] Phenolic resin was heated and melted at 50°C; then, phenolic resin and water were mixed at a mass ratio of 1:10 and placed in a hydrothermal reactor for the first hydrothermal reaction at 180°C for 10 hours; after the reaction was completed, the mixture was filtered, washed, and dried at 100°C for 5 hours to obtain a pre-crosslinked resin with a gel fraction of 68%.
[0062] A pre-crosslinked resin and water at a mass ratio of 1:11 were placed in a high-pressure reactor, and then transferred to a crucible furnace at 600℃ for a second hydrothermal reaction. During the reaction, the pressure in the high-pressure reactor was increased to 30 MPa within 5 minutes, and the reaction was maintained at this temperature for 4 hours. After the reaction was completed, the material was cooled, depressurized, washed, and dried to obtain a resin-based porous carbon material.
[0063] Example 7
[0064] Phenolic resin was heated and melted at 50°C; then, phenolic resin and water were mixed at a mass ratio of 1:10 and placed in a hydrothermal reactor for the first hydrothermal reaction at 160°C for 5 hours; after the reaction was completed, the mixture was filtered, washed, and dried at 100°C for 5 hours to obtain a pre-crosslinked resin with a gel fraction of 55%.
[0065] Pre-crosslinked resin and water at a mass ratio of 1:11 were placed in a high-pressure reactor, and then transferred to a crucible furnace at 600℃ for a second hydrothermal reaction. During the reaction, the pressure in the high-pressure reactor was increased to 30 MPa within 5 minutes, and the reaction was maintained at this temperature for 2 hours. After the reaction was completed, the material was cooled, depressurized, filtered, washed, and dried to obtain resin-based porous carbon material.
[0066] Example 8
[0067] Phenolic resin was heated and melted at 50°C; then, phenolic resin and water were mixed at a mass ratio of 1:10 and placed in a hydrothermal reactor for the first hydrothermal reaction at 150°C for 3 hours; after the reaction was completed, the mixture was filtered, washed, and dried at 100°C for 5 hours to obtain a pre-crosslinked resin with a gel fraction of 42%.
[0068] Pre-crosslinked resin and water at a mass ratio of 1:11 were placed in a high-pressure reactor, and then transferred to a crucible furnace at 600℃ for a second hydrothermal reaction. During the reaction, the pressure in the high-pressure reactor was increased to 30 MPa within 5 minutes, and the reaction was maintained at this temperature for 2 hours. After the reaction was completed, the material was cooled, depressurized, filtered, washed, and dried to obtain resin-based porous carbon material.
[0069] Comparative Example 1
[0070] Phenolic resin was heated and melted at 50°C; then, phenolic resin and water were mixed at a mass ratio of 1:10 and placed in a hydrothermal reactor for the first hydrothermal reaction at 180°C for 10 hours; after the reaction was completed, the mixture was filtered, washed, and dried at 100°C for 5 hours to obtain a pre-crosslinked resin with a gel fraction of 68%.
[0071] A pre-crosslinked resin and water at a mass ratio of 1:11 were placed in a high-pressure reactor, and then transferred to a crucible furnace at 450°C for a second hydrothermal reaction. During the reaction, the pressure in the high-pressure reactor increased to 15 MPa within 5 minutes, and the reaction was maintained at this temperature for 2 hours. After the reaction was completed, the material was cooled, depressurized, washed, and dried to obtain a resin-based porous carbon material.
[0072] Comparative Example 2
[0073] Phenolic resin was heated and melted at 50°C; then, phenolic resin and water were mixed at a mass ratio of 1:10 and placed in a hydrothermal reactor for the first hydrothermal reaction at 180°C for 10 hours; after the reaction was completed, the mixture was filtered, washed, and dried at 100°C for 5 hours to obtain a pre-crosslinked resin with a gel fraction of 68%.
[0074] Pre-crosslinked resin and water at a mass ratio of 1:11 were placed in a high-pressure reactor, and then the mixture was gradually heated to 600°C. The pressure in the high-pressure reactor was increased to 20 MPa within 60 minutes, and the reaction was maintained at this temperature for 2 hours. After the reaction was completed, the mixture was cooled, depressurized, washed, and dried to obtain resin-based porous carbon material.
[0075] Comparative Example 3
[0076] A mixture of phenolic resin and water at a mass ratio of 1:11 was placed in a high-pressure reactor, and then transferred to a crucible furnace at 600℃ for a second hydrothermal reaction. During the reaction, the pressure in the high-pressure reactor increased to 30 MPa within 5 minutes, and the reaction was maintained at this temperature for 2 hours. After the reaction was completed, the mixture was cooled, depressurized, washed, and dried to obtain a resin-based porous carbon material.
[0077] Comparative Example 4
[0078] The epoxy resin was heated to melt at 50°C; then, the epoxy resin was mixed with water at a mass ratio of 1:10 and placed in a hydrothermal reactor for the first hydrothermal reaction at 180°C for 10 hours; after the reaction was completed, the mixture was filtered, washed, and dried at 100°C for 5 hours to obtain a pre-crosslinked resin with a gel fraction of 35%.
[0079] Pre-crosslinked resin and water at a mass ratio of 1:11 were placed in a high-pressure reactor, and then transferred to a crucible furnace at 600℃ for a second hydrothermal reaction. During the reaction, the pressure in the high-pressure reactor was increased to 30 MPa within 5 minutes, and the reaction was maintained at this temperature for 2 hours. After the reaction was completed, the material was cooled, depressurized, filtered, washed, and dried to obtain resin-based porous carbon material.
[0080] Comparative Example 5
[0081] Furan resin was heated to melt at 50°C; then, the furan resin was mixed with water at a mass ratio of 1:10 and placed in a hydrothermal reactor for the first hydrothermal reaction at 180°C for 10 hours; after the reaction was completed, the mixture was filtered, washed, and dried at 100°C for 5 hours to obtain a pre-crosslinked resin with a gel fraction of 28%.
[0082] Pre-crosslinked resin and water at a mass ratio of 1:11 were placed in a high-pressure reactor, and then transferred to a crucible furnace at 600℃ for a second hydrothermal reaction. During the reaction, the pressure in the high-pressure reactor was increased to 30 MPa within 5 minutes, and the reaction was maintained at this temperature for 2 hours. After the reaction was completed, the material was cooled, depressurized, filtered, washed, and dried to obtain resin-based porous carbon material.
[0083] Comparative Example 6
[0084] The only difference between Comparative Example 6 and Example 1 is that: pre-crosslinked resin and water at a mass ratio of 1:6 were placed in a high-pressure reactor, and then transferred to a crucible furnace at 700°C for a second hydrothermal reaction. During the reaction, the pressure in the high-pressure reactor increased to 60 MPa within 5 minutes, and the reaction was maintained at this temperature for 3 hours. After the reaction was completed, the material was cooled, depressurized, washed, and dried to obtain resin-based porous carbon material.
[0085] The resin-based porous carbon materials prepared in the above examples and comparative examples were tested. The pore size was tested by nitrogen adsorption-desorption method (ASAP 2460 specific surface area and porosity analyzer), the specific surface area was tested by BET method, and the mechanical properties were tested by universal testing machine (INSTRON 5967). The results are shown in Table 1.
[0086] Table 1
[0087]
[0088] As can be seen from the comparison of Examples 1 to 4, short-term high pressure conditions are beneficial for preparing resin-based porous carbon materials with abundant micropores and mesopores, rich specific surface area and excellent mechanical strength. However, when the pressure is greater than 60 kPa, it will cause adverse effects such as over-activation of carbon skeleton leading to pore wall collapse, decrease in specific surface area and significant reduction in mechanical strength.
[0089] As can be seen from Examples 1 and 6, an excessively long second hydrothermal reaction time will affect the mechanical strength of the carbon skeleton and lead to increased material brittleness. This is because prolonged high-temperature and high-pressure treatment will cause excessive shrinkage of the carbon skeleton and propagation of microcracks.
[0090] As can be seen from Examples 1, 7 and 8, when the gel fraction of the pre-crosslinked resin is too small, its ability to stabilize the carbon skeleton is weak. This results in a decrease in the specific surface area, uneven development of the pore structure and a significant decrease in the mechanical strength of the prepared resin-based porous carbon material.
[0091] As can be seen from Example 1 and Comparative Example 1, when the pressure of the second hydrothermal reaction is lower than 20 MPa, it is difficult to generate supercritical water with a specific relative permittivity and ion product, which makes it difficult to induce the directional recombination of phenolic resin nanoparticles, thus making it impossible to obtain resin-based porous carbon materials with rich microporous and mesoporous structures.
[0092] As can be seen from Example 1 and Comparative Example 2, if the pressure increase rate of the second hydrothermal reaction is too slow, it will be impossible to form a non-equilibrium state of rapid cross-linking and directional stacking of particles, resulting in incomplete development of microporous structure, low mesoporous ratio, insufficient cross-linking degree of carbon skeleton, and poor mechanical strength.
[0093] As can be seen from Example 1 and Comparative Example 3, it is difficult to obtain the target resin-based porous carbon material by directly performing a short-time high-pressure hydrothermal reaction using phenolic resin. This is because the carbon skeleton of phenolic resin itself is unstable and cannot support the directional recombination of phenolic resin nanoparticles.
[0094] As can be seen from Example 1 and Comparative Examples 4-5, the resin-based porous carbon material prepared by the present invention requires phenolic resin as raw material. This is because phenolic resin has abundant active functional groups of hydroxymethyl and phenolic hydroxyl groups, which can undergo moderate cross-linking reaction under hydrothermal conditions to form a stable three-dimensional carbon skeleton. Epoxy resin and furan resin lack such active groups and are difficult to form a stable pre-cross-linked structure under hydrothermal conditions. Therefore, it is impossible to obtain porous carbon materials with excellent pore structure and mechanical properties.
[0095] As can be seen from Comparative Example 6, when the hot-press crosslinking coupling index is greater than 1500, the pore size of mesopores and micropores is larger, and the number of micropores differs greatly from the number of mesopores, resulting in poor mechanical strength of resin-based porous carbon materials. This indicates that there is a synergistic effect among the temperature, time and pressure of the second hydrothermal reaction, and optimizing any one parameter alone cannot obtain the best pore structure and mechanical properties.
[0096] The resin-based porous carbon material prepared in the above examples and comparative examples was used as the negative electrode active material to prepare a negative electrode sheet. Specifically, the resin-based porous carbon material, conductive carbon black, and sodium carboxymethyl cellulose were mixed in a mass ratio of 94:3:3. After adding solvent and grinding thoroughly, the mixture was coated onto the surface of copper foil, dried at 60°C for 20 hours, and sliced to obtain the negative electrode sheet. Lithium hexafluorophosphate was used as the lithium salt, and an electrolyte was prepared with a volume ratio of diethyl carbonate to ethylene carbonate of 1:1. A half-cell was assembled using a polypropylene (PP) separator, and its electrical performance was tested. The results are shown in Table 2.
[0097] Table 2
[0098]
[0099] As shown in Table 2, the resin-based porous carbon materials prepared by the method of this invention exhibit excellent electrochemical activity. The initial reversible specific capacity of the examples is higher than 398 mAh / g, and the capacity retention rate after 100 cycles is higher than 82%, which is significantly better than the comparative examples. Furthermore, the electrochemically active specific surface area (ECSA) measured by cyclic voltammetry shows that the ECSA of the examples is higher than 920 m² / g. 2 / g, far higher than the 420m in the comparative example. 2 / g~650m 2 / g indicates that the porous carbon prepared by this invention has more electrochemical active sites, and this performance mainly comes from the carboxyl groups and other functional groups abundant on its surface.
[0100] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0101] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing a resin-based porous carbon material, characterized in that, Includes the following steps: Phenolic resin was mixed with water and subjected to a first hydrothermal reaction to obtain a pre-crosslinked resin. The pre-crosslinked resin is mixed with water to carry out a second hydrothermal reaction to obtain a resin-based porous carbon material. During the second hydrothermal reaction, the system pressure reaches more than 20 MPa within 5 minutes. The gel fraction G of the pre-crosslinked resin, the system pressure P of the second hydrothermal reaction, the reaction temperature T of the second hydrothermal reaction, and the reaction time t of the second hydrothermal reaction satisfy the following relationship: K=(P×T×t) / G, where K is the thermo-compression crosslinking coupling index, and the value of K ranges from 250 to 1500.
2. The method for preparing resin-based porous carbon material according to claim 1, characterized in that, The gel fraction G of the pre-crosslinked resin is 50%~85%.
3. The method for preparing resin-based porous carbon material according to claim 1, characterized in that, The temperature of the first hydrothermal reaction is 150℃~200℃; the time is 3h~7h.
4. The method for preparing resin-based porous carbon material according to any one of claims 1 to 3, characterized in that, The mass ratio of the phenolic resin to water is 1:5 to 1:
15.
5. The method for preparing resin-based porous carbon material according to claim 1, characterized in that, During the second hydrothermal reaction, the system pressure P reaches 20 MPa to 60 MPa within 5 minutes.
6. The method for preparing resin-based porous carbon material according to claim 1, characterized in that, The reaction temperature T of the second hydrothermal reaction is 500℃~700℃.
7. The method for preparing resin-based porous carbon material according to claim 6, characterized in that, The reaction time t for the second hydrothermal reaction is 1h to 3h.
8. The method for preparing resin-based porous carbon material according to any one of claims 5 to 7, characterized in that, The mass ratio of the pre-crosslinked resin to water is 1:5 to 1:
20.
9. A resin-based porous carbon material prepared by the method of any one of claims 1 to 8, wherein the micropores in the resin-based porous carbon material have a diameter of less than 2 nm, the mesopores have a diameter of 2 nm to 8 nm, the ratio of the number of micropores to the number of mesopores is 4:1 to 4:3, and the specific surface area of the resin-based porous carbon material is 1400 m². 2 / g~2200m 2 / g.
10. The application of the resin-based porous carbon material as described in claim 9 in silicon-carbon anodes, supercapacitive electrodes, or solid-state batteries.